Emerging Technologies in Data Mining and Information Security Proceedings of IEMIS 2018, Volume 2 - Abraham, Ajith; Dutta, Paramartha; Mandal, Jyotsna Kumar; Bhattacharya, Abhishek; Dutta, Soumi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book features research papers presented at the International Conference on Emerging Technologies in Data Mining and Information Security (IEMIS 2018) held at the University of Engineering & Management, Kolkata, India, on February 23-25, 2018. It comprises high-quality research by academics and industrial experts in the field of computing and communication, including full-length papers, research-in-progress papers, case studies related to all the areas of data mining, machine learning, IoT and information security.
The Study of Sentimental State of Human from Tweet Text -- Data Analytic Techniques with Hardware Based Encryption for High Profile Dataset -- Exploring Student Migration in Rural Region of Bangladesh -- Analysis on Lightning News And Correlation With Lightning Imaging Sensor (LIS) Data -- Design of Business Canvas Model for Social Media -- EEG Signal Analysis Using Different Clustering Techniques -- Viable Crop Prediction Scenario in Big Data Using a Novel Approach -- A Graph Based Approach on Extractive Summarization -- Promises and Challenges of Big Data in a Data Driven World -- A Proposed Approach for Improving Hadoop Performance For Handling Small Files -- Identification of the Recurrence of Breast Cancer by Discriminant Analysis -- Spam Detection in SMS based on Feature Selection Techniques -- Analysis and Design of an Efficient Temporal Data Mining Model for the Indian Stock Market -- Community Detection Methods in Social Network Analysis -- A Comparative Study on Cluster Analysis of Micro-Blogging Data.
Keywords: Computational intelligence; Artificial intelligence; Data protection; Computational Intelligence; Artificial Intelligence; Data and Information Security